‘I felt I belonged’: A qualitative study of role modelling and team integration as key drivers of primary care career choice - Eva Pfarrwaller; Camille Laurent; Johanna Sommer; Anne Baroffio; Dagmar M. Haller; Hubert Maisonneuve (European Journal of General Practice)
Background Clinical placements significantly impact medical students’ career choices. Primary care physicians supervising these placements can influence students’ career decisions through role modelling and by creating supportive learning environments.Objectives This qualitative study aimed to identify factors contributing to role modelling and students’ sense of integration during placements and their influence on career decisions, with a focus on primary care.Methods Semi-structured interviews were conducted with postgraduate trainees selected based on interest in primary care, exploring their experiences during undergraduate clinical placements and factors influencing career choices. Data were thematically analysed to identify key themes related to student integration, well-being, and supervisor role modelling.Results Analysis revealed four key domains where primary care physicians can positively influence students’ career interest: onboarding students effectively, fostering positive and inclusive team dynamics, involving students in patient care, and providing high-quality supervision and feedback. Students reported that feeling valued and socially included contributed to their well-being and professional self-efficacy, which in turn impacted their career choices.Conclusion Supportive and inclusive learning environments during placements are critical to fostering students’ professional growth. While relevant across clinical settings, this study’s findings hold particular significance for primary care due to the challenge of balancing clinical and practice management duties and teaching. Implementing structured onboarding, team integration, and effective supervision can enhance students’ experiences and promote interest in primary care. Future research should extend these findings beyond primary care. The proposed roadmap could both spark interest in primary care and promote future collaboration between primary and secondary care.